The Effect of Neoalgae Spirulina Supplements Intakes on Increasing Body Height and Weight of Stunting Children in Mranggen, Sukoharjo, Central Java - Nur Ani; Nine Elissa Maharani; Farid Setyo Nugraho; Budhi Rahardjo; Amrih Gancar Utami (Journal of Epidemiology and Public Health, 2023)
Background: Children who are stunted have a higher risk of experiencing health and brain development disorders, and have a lower likelihood of achievement and a bright future. Spirulina is one of the food sources enriched with nutrients that affect the nutritional status of children. The study aims to discover the effect of the administration of Spirulina Neoalgae supplements on increasing the height and weight of stunting toddlers in Mranggen village. Subjects dan Method: The study used a quasi-experimental design conducted in Mranggen Village, Sukoharjo, Central Java. A total of 100 toddlers selected using total sampling were included in this study. The independent variable in this study was the intervention of Spirulina Neoalgae supplements and the dependent variables in this study were body weight and height. Toddlers were given supplement interventions for 4 weeks. The collected data were subsequently analyzed using the Paired-Test. Results: Before the intervention the average height was (Mean= 82.92; SD = 8.77) and body weight was (Mean= 9.97; SD= 2.09). After the supplement intervention for 2 weeks, the average height was (Mean= 83.56; SD = 8.61) and body weight was (Mean= 10.11; SD= 2.07). Average height (Mean= 84.56; SD= 8.57) and body weight (Mean= 11.04; SD = 2.10) in week four increased and the result was statistically significant (p <0.001). Conclusion: The administration of neoalgae supplements affects increasing height and weight in stunted children in Mranggen Village, Sukoharjo, Central Java. Keywords: Supplements, Neoalgae, Nutritional Status, Height, Weight, Stunting